2007
DOI: 10.1021/es0706089
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Analysis Reveals Lower-Order River Dissolved Inorganic Carbon Pools Are Highly Dynamic

Abstract: River systems draining peaty catchments are considered a source of atmospheric CO2,thus understanding the behavior of the dissolved inorganic carbon pool (DIC) is valuable. The carbon isotopic composition, delta13C(DIC), and concentration, [DIC], of fluvial samples collected diurnally, over 14 months, reveal the DIC pools to be dynamic in range (-22 to -4.9% per hundred, 0.012 to 0.468 mmol L(-1) C), responding predictably to environmental influences such as changing hydrologic conditions or increased levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
113
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(125 citation statements)
references
References 27 publications
12
113
0
Order By: Relevance
“…It was also obvious that the hydrology has an influence on the level of EpCO 2 . At low flow, DIC concentration is highest (Waldron et al 2007) and biological activity is greatest (as temperature tends to be higher); event flow, whilst flushing out soil CO 2 so increasing the pool size, ultimately dilutes the DIC pool and so lowers saturation of dissolved carbon dioxide. Turbulent waters and colder temperatures reduce biological activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was also obvious that the hydrology has an influence on the level of EpCO 2 . At low flow, DIC concentration is highest (Waldron et al 2007) and biological activity is greatest (as temperature tends to be higher); event flow, whilst flushing out soil CO 2 so increasing the pool size, ultimately dilutes the DIC pool and so lowers saturation of dissolved carbon dioxide. Turbulent waters and colder temperatures reduce biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Incised catchment slopes have the most freely-draining humus iron podzols (<1 m deep); the main river valley bottoms generally have freely draining alluvial deposits. For a detailed description of the study site and its geology and climate characteristics, see Waldron et al (2007).…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Hope et al (2004) reached similar conclusions using fortnightly sampling of riverine pCO 2 from a peatland catchment in the UK. There is clearly promise in using fluvial DIC to infer changes in catchment productivity but higher temporal resolution work has shown that variation can be significant over diurnal time scales (e.g., Waldron et al 2007;Parker et al 2007), thus a method is required to quantify this variation over long time scales and at high resolution.…”
mentioning
confidence: 99%